Modern strategies for regulating the motor activity of preschool and school age children in the educational space - L.N. Voloshina; V.L. Kondakov; A.A. Tretyakov; E.N. Kopeikina; M. Cretu; V. Potop (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: the systematization of modern strategies for regulating the motor activity of preschool and school-age children. The criteria for assessing motor activity taking into account the individual characteristics of children and sociocultural conditions are considered. The adaptive strategy of regulation of the motor activity of a growing person in modern educational space is substantiated. Material: 10 theses and more than 80 papers published in specialized journals of Russia, Ukraine, Kazakhstan, Belarus were analyzed. In the article is used quantitative approach, which has research and descriptive character. This approach includes methods for examining documents. The identification of studies over the past 50 years has been carried out. The analysis of normative program-methodological materials, educational standards, exemplary educational programs and the results of their own research was carried out. These studies substantiated various approaches to regulating and forming positive dynamics of motor activity in preschool and school-age children. Results: Three strategies for regulating motor activity were identified: biological, value-social and biosocial (adaptive). Their compliance with the level of scientific and methodological knowledge and domestic experience is established. The limiting factors have been established and ways of transforming the system of physical education at different levels of education have been concretized. The modern adaptive strategy of regulation of the motor activity of preschool children and younger schoolchildren is substantiated. The expediency of its introduction into the educational process is shown. This creates a favorable environment for the physical development of children. Conclusion: The adaptive system for regulating motor activity should take into account: the interests and opportunities of children at all levels of the educational system; regional sports traditions; sociocultural and climatic conditions. It is extremely important to recreate the playing space of childhood. This contributes to the formation of an active position in relation to the physical culture of the individual.